Applied numerical methods with MATLAB for engineers and scientists - Chapra, Steven C. (McGraw Hill Education, 2023)
Applied Numerical Methods with MATLAB is designed to support a one-semester course in numerical methods. It has been written for students who want to learn and apply numerical methods in order to solve problems in engineering and science. As such, the methods are motivated by problems rather than by mathematics. That said, sufficient theory is provided so students come away with insight into the techniques and their shortcomings.